Hypoxia inducible factor (HIF) activity reporter cell line - Shafee, Norazizah; Stanbridge, Eric J.; Yusoff, Khatijah; Sien, Yei Liew (2012)
The present invention relates to the construction of a new hypoxia inducible factor (HIF) responsive reporter gene construct, the genetic constructs and vectors containing the same. Further, the present invention relates to a stable cell line comprising the HIF responsive reporter construct, as well as methods and uses of the inventive constructs and cell lines to identify modulators of HIF activity.